Semitransparent ZnO/PEDOT based hybrid inorganic/organic heterojunction thin dilm diodes prepared combined RF magnetron sputtering and elctrodeposition technique - Rodriguez-Moreno, Jorge; Navarrete-Astorga, Elena; Martín-Jiménez, Francisco de Paula; Schrebler, Ricardo; Ramos-Barrado, José R.; Dalchiele, Enrique A. (Elsevier, 2012)
n-ZnO/p-poly(3,4-ethylenedioxythiophene) (PEDOT) semitransparent inorganic–organic hybrid vertical heterojunction thin film diodes have been fabricated with PEDOT and ZnO thin films grown by electrodeposition and radio-frequency magnetron-sputtering respectively, onto a tin doped indium oxide coated glass substrate. The diode exhibited an optical transmission of ~ 40% to ~ 50% in the visible region between 450 and 700 nm. The current–voltage (I–V) characteristics of the heterojunction show good rectifying diode characteristics, with a ratio of forward current to the reverse current as high as 35 in the range − 4 V to + 4 V. The I–V characteristic was examined in the framework of the thermionic emission model. The ideality factor and barrier height were obtained as 4.0 and 0.88 eV respectively.
Keywords: Física aplicada; Semitransparent heterojunction; n-ZnO; PEDOT; sputtering; electrodeposition